Content analysis of the independent curriculum physics science textbook from the perspective of critical thinking aspects and HOTS - Sebastian, Rio; Jumadi, Jumadi; Winingsih, Puji Hariati; Hapsari, Nadya Amalia Putri (Momentum: Physics Education Journal, 2023)
This study aims to reveal characteristics of critical thinking and cognitive elements in HOTS category questions from the Independent Curriculum Senior High School Physics Science Textbook in the material of Magnitudes and Measurements. This content analysis study employs the descriptive analysis method, as well as qualitative and quantitative approaches. The Science Textbook Physics independent curriculum for class X Senior High School was utilized as the study's sample. According to the findings of this study, the two text books evaluated elevate critical thinking features such as interpretation, analysis, evaluation, explanation, inference, and self-regulation, with the aspect of interpretation prevailing at 35.14% in book A and 33.35% in book B. While the findings of the HOTS category question analysis for both books revealed that both books discovered HOTS category questions with components of analyzing (C4) and evaluating (C5), no HOTS categories were discovered for the element of creating (C6). Most of the problems in the two books are still dominated by LOTS (low order thinking skill) questions, indicating that learning to think at a higher level requires more than just textbooks and direct instruction from the teacher. As a result, in order for students to think at a higher level, direct instruction from the teacher is required.